Mathematical model and stability of SWCNT- and MWCNT-based nanofluid flow with thermal and chemically reactive effects inside a porous vertical cone - Xu, Haihua; Awwad, Fuad A.; Ismail, Emad A. A.; Khan, Waris (Frontiers in Chemistry, 2025)
In this study is to investigate the significance of single walled (SWCNTs) and multi walled (MWCNTs) with convectional fluid (water) over a vertical cone under the influences of chemical reaction, magnetic, thermal radiation, and saturated porous media. The impact of heat source is also examined.Based on the flow assumptions, the fundamental flow characteristics are modeled in term of partial differential equations (PDEs). Using the appropriate transformation, the PDEs are denationalized in term of conventional derivatives (ordinary differential equations), and then solved via RK4 in MATLAB. For confirmation the results, a comparison is carried out with previous investigated problem and brilliant agreement is established. The emerging dimensionless physical factors impacts on flow problem are deliberated through graphs and tables. The solution of the present analysis reveals the dual solution for the suction and injection parameter is occurred. Therefore, the stability exploration is implemented to confirm the stable solution. The aim of the study is to analysis the SWCT and MWCTs in vertical cone with stability to establish that only the first solution is a reliable solution. The consequence of the present analyses signifies that large volume fraction subsidized to increase the nanofluid movement. From the mathematical model and graphical demonstration, it is noted that velocity of MWCNTs is higher than SWCNTs. Moreover, it is witnessed that the local skin friction (LSF), rate of heat transfer, Nusselt number (NN), and Sherwood number (SN) improve with Biot number (BN).